Trade Competitiveness Diagnostic Toolkit - Reis, Jose Guilherme; Farole, Thomas (World Bank, 2012)
This Trade Competitiveness Diagnostic (TCD) toolkit provides a framework, guidelines, and practical tools needed to conduct an analysis of trade competitiveness. The toolkit can be used to assess the competitiveness of a country's overall basket of exports, as well as specific traded sectors. It includes guidance on a range of tools and indicators that can be used to analyze trade performance in terms of growth, orientation, diversification, quality, and survival, as well as quantitative and qualitative approaches to analyze the market and supply-side factors that determine competitiveness. The toolkit facilitates the identification of the main constraints to improved trade competitiveness and the policy responses to overcome these constraints. The output of a TCD initiative can be used for a wide variety of purposes. The TCD toolkit is intended for policy makers and practitioners involved in analysis of trade performance and design of trade and industrial policy.